Guidance on the risk assessment of substances present in food intended for infants below 16 weeks of age. (31st May 2017) - ,; Hardy, Anthony; Benford, Diane; Halldorsson, Thorhallur; Jeger, Michael John; Knutsen, Helle Katrine; More, Simon; Naegeli, Hanspeter; Noteborn, Hubert; Ockleford, Colin; Ricci, Antonia; Rychen, Guido; et al.
Abstract: Following a request from the European Commission to EFSA, the EFSA Scientific Committee (SC) prepared a guidance for the risk assessment of substances present in food intended for infants below 16 weeks of age. In its approach to develop this guidance, the EFSA SC took into account, among others, (i) an exposure assessment based on infant formula as the only source of nutrition; (ii) knowledge of organ development in human infants, including the development of the gut, metabolic and excretory capacities, the brain and brain barriers, the immune system, the endocrine and reproductive systems; (iii) the overall toxicological profile of the substance identified through the standard toxicological tests, including critical effects; (iv) the relevance for the human infant of the neonatal experimental animal models used. The EFSA SC notes that during the period from birth up to 16 weeks, infants are expected to be exclusively fed on breast milk and/or infant formula. The EFSA SC views this period as the time where health‐based guidance values for the general population do not apply without further considerations. High infant formula consumption per body weight is derived from 95th percentile consumption. The first weeks of life is the time of the highest relative consumption on a body weight basis. Therefore, when performing an exposure assessment, the EFSA SC proposes to use the high consumption value of 260 mL/kg bw per day. A decision tree approach is proposed that enables a risk assessment of substances present in food intended for infants below 16 weeks of age. The additional information needed when testing substances present in food for infants below 16 weeks of age and the approach to be taken for the risk assessment are on a case‐by‐case basis, depending on whether the substance is added intentionally to food and is systemically available. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1248/full